The Role and Application of 'Urf as a Source of Islamic Law: A Historical Review and Fiqhiyah Rules - Muhammad Husni Abdulah Pakarti; Ending Solehudin; Maruf Maruf; Iqbal Saujan; Saeideh Shakibiciu (Yayasan Cendekia Gagayunan Indonesia, 2025)
Urf or community customs have an important role in the development of Islamic law. As one of the sources of law, 'urf is recognized in fiqhiyah rules as long as it does not contradict the shar'i nash. This research aims to analyze the role and application of 'urf in Islamic law with a historical approach and examine the fiqhiyah rules related to its use. This research uses a qualitative approach with a literature study method. Data were collected from primary and secondary sources, such as classical fiqh books, academic journals, and Islamic legal literature. The analysis is done descriptively-critically to understand the historical development of 'urf and its relevance in fiqhiyah rules. The results show that 'urf has a significant role in the development of Islamic law, especially in the context of legal adaptation to social and cultural changes. Historically, 'urf has been used by scholars as a basis in determining laws that are relevant to the context of society, as long as they do not conflict with the principles of sharia. Fiqhiyah rules such as al-'ādah muhakkamah (customs can be made into law) and Al-maslahah al-mursalah (interests that are not mentioned by the nash) become the main basis for applying 'urf. This finding confirms that 'urf can be a valid source of Islamic law as long as it meets certain criteria, such as not contradicting shar'i arguments and being common in society. Understanding 'urf is also important in the context of fatwa and contemporary Islamic legal policy. 'Urf acts as a dynamic instrument in Islamic law that allows flexibility in the application of sharia in accordance with social reality. This study contributes to understanding how Islamic law can remain relevant by considering the customs of society that do not contradict the principles of sharia.